Monitoring the impact of COVID-19 in Myanmar: Urban food retailers - Late July 2020 survey round - Maredia, Mywish K.; Goeb, Joseph; Lambrecht, Isabel B.; Masias, Ian; Win, Khin Zin (International Food Policy Research Institute, 2020)
This is the second policy note in a series presenting results from rounds of a telephone survey of a sample of retail food shop owners or managers located in two cities in Myanmar – Yangon, the economic center of the country with 4.4 million inhabitants, and Mandalay, the second largest city with 1.1 million inhabitants. The phone surveys are designed to better understand the effects of COVID-19 shocks on Myanmar’s agri-food marketing system from the perspective of these smallscale urban food retailers. Their shops are an important outlet for final consumers to purchase a variety of consumer goods, including many types of processed and packaged dry foods, condiments, snacks, beverages, basic staple grains (i.e., rice and pulses), dairy products, eggs, kitchen crops, tobacco, and alcohol products. The COVID-19 economic crisis could bring dramatic changes to these retailers – not only on the demand side in terms of the food purchasing behaviors of consumers, but also on the supply side in terms of how the food supply chains upon which they rely function and how they respond to these changes. This policy note builds on the analysis of the firstround of the survey, which focused on the demand side and overall business effects of COVID-19, by adding detailed questions on three additional themes – supplier options, credit extended and received by retailers, and the use of modern technologies and practices.